On the incorporation of waste ceramic powder into concrete - Alotaibi, Jasem G.; Alajmi, Ayedh Eid; Alsaeed, Talal; Khalaf, Jamal A.; Yousif, Belal F. (Frontiers in Mechanical Engineering, 2024)
This study investigates the potential use of waste ceramic powder as a filler in concrete. Different percentages of waste ceramic powder were added to the concrete, and the compressive strength and water absorption properties were assessed. Failure mechanisms were analyzed using scanning electron microscopy (SEM). The findings revealed that incorporating 5% ceramic powder into concrete increased its compressive strength by approximately 12.5%. However, adding more than 5% ceramic powder led to a proportional decrease in strength. Additionally, water absorption increased when the ceramic content exceeded 5%. SEM analysis showed that higher ceramic content weakened the adhesion of the ceramic particles, and noticeable aggregation was observed.